The Yin and Yang of epigenetics in the field of nanoparticles. Issue 4 (24th January 2022) - Musolino, Elettra; Pagiatakis, Christina; Serio, Simone; Borgese, Marina; Gamberoni, Federica; Gornati, Rosalba; Bernardini, Giovanni; Papait, Roberto
Abstract : Evaluating the role of epigenetics in the field of NPs: first, the role of epigenetics in mediating nanotoxicity, and second, the possibility of using NPs for delivery of "epi-drugs" to overcome their limitations. Abstract : Nanoparticles (NPs) have become a very exciting research avenue, with multitudinous applications in various fields, including the biomedical one, whereby they have been gaining considerable interest as drug carriers able to increase bioavailability, therapeutic efficiency and specificity of drugs. Epigenetics, a complex network of molecular mechanisms involved in gene expression regulation, play a key role in mediating the effect of environmental factors on organisms and in the etiology of several diseases ( e.g., cancers, neurological disorders and cardiovascular diseases). For many of these diseases, epigenetic therapies have been proposed, whose application is however limited by the toxicity of epigenetic drugs. In this review, we will analyze two aspects of epigenetics in the field of NPs: the first is the role that epigenetics play in mediating nanotoxicity, and the second is the possibility of using NPs for delivery of "epi-drugs" to overcome their limitations. We aim to stimulate discussion among specialists, specifically on the potential contribution of epigenetics to the field of NPs, and to inspire newcomers to this exciting technology.